Plasma nitriding of steels - Aghajani, Hossein; Behrangi, Sahand (Springer, 2017)
This book focuses on the effect of plasma nitriding on the properties of steels. Parameters of different grades of steels are considered, such as structural and constructional steels, stainless steels and tools steels. The reader will find within the text an introduction to nitriding treatment, the basis of plasma and its roll in nitriding. The authors also address the advantages and disadvantages of plasma nitriding in comparison with other nitriding methods.
Keywords: Steel -- Nitrogen content.; Nitriding.; Plasma engineering.; elektronické knihy; electronic books